Self-pressurized rapid rreezing as cryo-fixation method for electron microscopy and cryopreservation of living cells - Hübinger, Jan; Grabenbauer, Markus (Current protocols in cell biology, 2018)
Reduction or complete prevention of ice crystal formation during freezing of biological specimens is mandatory for two important biological applications: (1) cryopreservation of living cells or tissues for long-term storage, and (2) cryo-fixation for ultrastructural investigations by electron microscopy. Here, a protocol that is fast, easy-to-use, and suitable for both cryo-fixation and cryopreservation is described. Samples are rapidly cooled in tightly sealed metal tubes of high thermal diffusivity and then plunged into a liquid cryogen. Due to the fast cooling speed and high-pressure buildup internally in the confined volume of the metal tubes, ice crystal formation is reduced or completely prevented, resulting in vitrification of the sample. For cryopreservation, however, a similar principle applies to prevent ice crystal formation during re-warming. A detailed description of procedures for cooling (and re-warming) of biological samples using this technique is provided. © 2018 by John Wiley & Sons, Inc.
Gesehen am 30.04.2020